2013
DOI: 10.3389/fpsyg.2013.00304
|View full text |Cite
|
Sign up to set email alerts
|

Conscious Experience and Episodic Memory: Hippocampus at the Crossroads

Abstract: If an instance of conscious experience of the seemingly objective world around us could be regarded as a newly formed event memory, much as an instance of mental imagery has the content of a retrieved event memory, and if, therefore, the stream of conscious experience could be seen as evidence for ongoing formation of event memories that are linked into episodic memory sequences, then unitary conscious experience could be defined as a symbolic representation of the pattern of hippocampal neuronal firing that e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
41
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 144 publications
5
41
0
1
Order By: Relevance
“…orbitofrontal cortex and ventral striatum), these mesolimbic regions comprise a reward processing system(3) that allows us to anticipate, respond to, and learn from reward outcomes in quotidian life. Whereas ventral/anterior hippocampus is intrinsically connected to ventral striatum(4), processes reward-related information, and is preferentially involved in anxiety(5), dorsal/posterior hippocampus preferentially processes spatial information(6). Using an ecologically valid task of reward-based spatial learning adapted from animal research, we sought to identify functional impairments in mesolimbic and ventral striatal circuitry that may contribute to OCD behaviors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…orbitofrontal cortex and ventral striatum), these mesolimbic regions comprise a reward processing system(3) that allows us to anticipate, respond to, and learn from reward outcomes in quotidian life. Whereas ventral/anterior hippocampus is intrinsically connected to ventral striatum(4), processes reward-related information, and is preferentially involved in anxiety(5), dorsal/posterior hippocampus preferentially processes spatial information(6). Using an ecologically valid task of reward-based spatial learning adapted from animal research, we sought to identify functional impairments in mesolimbic and ventral striatal circuitry that may contribute to OCD behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty-one of these individuals were treatment naïve and 12 were off psychotropic medications for at least 12 weeks. Given findings of functional deficits in reward processing circuits(9) and compensatory hippocampal engagement during other learning tasks(22) in OCD, together with the differential roles of posterior and anterior hippocampus in processing spatial and reward information, respectively(6), we made the following hypotheses. First, we hypothesized that whereas both groups would engage tempoparietal areas while navigating the maze, OCD participants would over-engage posterior hippocampus during spatial learning.…”
Section: Introductionmentioning
confidence: 99%
“…These preliminary findings are in value in supporting the role of the so-called mental frame syncing in the spatial processing [21,22], namely a cognitive process that permits an effective retrieval by the synchronization of the two types of allocentric representations [23], the viewpoint-independent representation (i.e., including object-to-object information) and the allocentric viewpoint-dependent representation (i.e., including information about egocentric current heading). Some evidence has shown that two regions within the hippocampus are specifically involved in the processing of allocentric information [24,25].…”
Section: Introductionmentioning
confidence: 68%
“…The second region consists of the neurons in CA1, which receives inputs from CA3 via Schaffer's collaterals and encodes allocentric representations involving only abstract, object-to-object information. This is what Behrendt calls allocentric viewpoint-independent representation [23].…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation